2010
DOI: 10.1063/1.3295558
|View full text |Cite
|
Sign up to set email alerts
|

Unification Of The Phonon Mode Behavior In Semiconductor Alloys

Abstract: We demonstrate how to overcome serious problems in understanding and classification of vibration spectra in semiconductor alloys, following from traditional use of the virtual crystal approximation (VCA). We show that such different systems as InGaAs (1-bond→1-mode behavior), InGaP (modified 2-mode) and ZnTeSe (2-bond→1-mode) obey in fact the same phonon mode behavior -hence probably a universal one -of a percolation-type (1-bond→2-mode). The change of paradigm from the 'VCA insight' (an averaged microscopic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Thinking about the mass differences between Ga and Mn atoms, the obtained results show that it would be difficult to obtain a ‘two-mode’ behavior as that verified in our previous calculations for the Al x Ga 1− x N alloys [20]. However, considering the position of the Mn impurity mode in the percolation model developed by Pagès and co-workers [11],…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Thinking about the mass differences between Ga and Mn atoms, the obtained results show that it would be difficult to obtain a ‘two-mode’ behavior as that verified in our previous calculations for the Al x Ga 1− x N alloys [20]. However, considering the position of the Mn impurity mode in the percolation model developed by Pagès and co-workers [11],…”
Section: Resultsmentioning
confidence: 67%
“…We can attribute this discrepancy to the fact that Mn induces local distortions in the GaAs lattice [19], giving rise to local modes, which were detected only in ion-implanted sample experiments [9], and it is not predicted by the VCA model. We would like to point out that in the VCA model, no singularity is expected on the TO modes, and then, the TO frequencies shift regularly between the natural frequency in the pure crystal and the impurity frequency [11]. Moreover, the most stable structure of MnAs is the hexagonal NiAs modification [17], for which the local environment of the Mn atoms is quite different from that found in the zincblende structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the alloy exhibits an unusually large contrast in physical properties manifesting in bond stiffness and bond-lengths distribution of its constituting bonds, leading to a uniquely well-resolved 1-bond-2-mode behavior as already reported in the Raman spectra of this system [10]. From such studies it is well established that various defect dissemination mechanisms in ZnSe are signi�cantly reduced on increasing the lattice rigidity and for the reason that high degree of covalent bonding of Be chalcogenides can lead to an increase of shear modulus in such ternaries [10]. Following this, the mixing of Be chalcogenides with other II-VI binary compounds is a widely accepted procedure for increasing solid solution hardening, and the structural resistance.…”
Section: Introductionmentioning
confidence: 78%
“…Previously, fundamental defects in as grown ZnBeSe (ZBS) materials are studied with a positron spectroscopy and the defects responsible for the photoluminescence decay among the compositionally assorted samples are identi�ed in detail [9]. It is found that the alloy exhibits an unusually large contrast in physical properties manifesting in bond stiffness and bond-lengths distribution of its constituting bonds, leading to a uniquely well-resolved 1-bond-2-mode behavior as already reported in the Raman spectra of this system [10]. From such studies it is well established that various defect dissemination mechanisms in ZnSe are signi�cantly reduced on increasing the lattice rigidity and for the reason that high degree of covalent bonding of Be chalcogenides can lead to an increase of shear modulus in such ternaries [10].…”
Section: Introductionmentioning
confidence: 98%